2017
DOI: 10.4172/2165-7548.1000350
|View full text |Cite
|
Sign up to set email alerts
|

Happiness: Role of Dopamine and Serotonin on Mood and Negative Emotions

Abstract: Dopamine is a hormone associated with happiness and serotonin regulates our mood. When a person is physically attracted to another, an activation of dopamine, serotonin increased and production of oxytocin, a hormone that reduces pain perception and increases the emotional connection we have with the other occurs. Disconnecting the amygdala, the parts of the brain that are active against negative emotions like fear. The combination of all these elements leads to crush the other. After our beliefs, the way we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Endocrinological research shows that when we feel connected, socially included, and bonded, our bodies secret oxytocin, helping us feel safe and loved [ 28 ]. Social rejection or ostracism can cause tremendous social pain, which is similar to the reactions to physical pain [ 29 ]. People having a strong sense of belonging to a social group are happier and more satisfied with their health status [ 30 ].…”
Section: Results Regarding the Strategies To Build Resiliencementioning
confidence: 99%
“…Endocrinological research shows that when we feel connected, socially included, and bonded, our bodies secret oxytocin, helping us feel safe and loved [ 28 ]. Social rejection or ostracism can cause tremendous social pain, which is similar to the reactions to physical pain [ 29 ]. People having a strong sense of belonging to a social group are happier and more satisfied with their health status [ 30 ].…”
Section: Results Regarding the Strategies To Build Resiliencementioning
confidence: 99%
“…Even though it is found in low to moderate concentrations in beers, this alkaloid contributes to the diuretic effect of beer and provides some bitterness characteristics [ 16 , 18 ]. Regarding the effects of hordenine in humans, it has been reported to increase heart rate and blood pressure [ 19 ] as well as to stimulate the release of dopamine, which has been related to happiness [ 15 , 20 ]. On the other hand, other authors have concluded that beer flavors are the main factor responsible for dopamine release [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala interprets the information in order to determine the emotion that should be linked to the positive emotions or negative emotions in learning. All of the information will be transmitted to frontal cortex, the outermost, frontal area of the brain [19,27,29]. The frontal cortex processes the information and helps the brain to determine if it already knows something about the information that is being perceived.…”
Section: Resultsmentioning
confidence: 99%
“…Emotion is the result of outer stimulus that interacts with subjective feelings, physiological reaction and behaviour [18,25]. There are several perspcetives to understand the situation and emotional changes [19,26,27,38] which are: (1) subjective approach that can assess feelings and experiences that one have gone through and (2) understanding through behaviour, facial expression and gestural. This is align with a theory of how the mind interprets the verbal, written and teaching materials that are related to Mathematics could influence the brain and emotions to learn Mathematics [38].…”
Section: Literature Reviewmentioning
confidence: 99%